Evolutionary Implications of Dental Eruption in Dasypus (Xenarthra) - Ciancio, Martín Ricardo (2012)
Late eruption of the permanent dentition was recently proposed as a shared anatomical feature of endemic African mammals (Afrotheria), with anecdotal reports indicating that it is also present in dasypodids (armadillos). In order to clarify this question, and address the possiblity that late eruption is shared by afrotherians and dasypodids, we quantified the eruption of permanent teeth in Dasypus, focusing on growth series of D. hybridus and D. novemcinctus. This genus is the only known xenarthran that retains two functional generations of teeth. Its adult dentition typically consists of eight upper and eight lower ever-growing (or euhypsodont) molariforms, with no premaxillary teeth. All but the posterior-most tooth are replaced, consistent with the identification of a single molar locus in each series. Comparison of dental replacement and skull metrics reveals that most specimens reach adult size with none or few erupted permanent teeth. This pattern of growth occurring prior to the full eruption of the dentition is similar to that observed in most afrotherians. The condition observed in Dasypus and many afrotherians differs from that of most other mammals, in which the permanent dentition erupts during (not after) growth, and is complete at or near the attainment of sexual maturity and adult body size. The suture closure sequence of basicranial and postcranial epiphyses does not correlate well with dental eruption. The basal phylogenetic position of the taxon within dasypodids suggests that diphyodonty and late dental replacement represent the condition of early xenarthrans. Additionally, the inferred reduction in the number of molars to a single locus and the multiplication of premolars represent rare features for any living mammal, but may represent apomorphic characters for Dasypus.